2007
DOI: 10.1016/j.dam.2005.05.044
|View full text |Cite
|
Sign up to set email alerts
|

An efficiently computed lower bound on the number of recombinations in phylogenetic networks: Theory and empirical study

Abstract: Phylogenetic networks are models of sequence evolution that go beyond trees, allowing biological operations that are not tree-like. One of the most important biological operations is recombination between two sequences. An established problem [J. Hein, Reconstructing evolution of sequences subject to recombination using parsimony, Math. Biosci. 98 (1990) 185-200; J. Hein, A heuristic method to reconstruct the history of sequences subject to recombination, J. Molecular Evoluation 36 (1993) 396-405;Y. Song, J. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The algorithmic problem of reconstructing a history of recombination events (with mutations), or determining the minimum number of recombination nodes needed in a phylogenetic network (for both rooted and unrooted problems), has been studied in a number of papers (Gusfield et al, 2007;Hein, 1990Hein, , 1993Hein, 2003, 2004;Wang et al, 2001;Myers and Griffiths, 2003;Hudson and Kaplan, 1985;Kececioglu and Gusfield, 1998;Gusfield, 2005a;Gusfield et al, 2004b,a;Nakhleh et al, 2003Nakhleh et al, , 2004Moret et al, 2004;Bansal, 2004, 2006a;Lyngso et al, 2005;Song et al, 2006;Myers, 2003).…”
Section: Rooted and Root-unknown Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The algorithmic problem of reconstructing a history of recombination events (with mutations), or determining the minimum number of recombination nodes needed in a phylogenetic network (for both rooted and unrooted problems), has been studied in a number of papers (Gusfield et al, 2007;Hein, 1990Hein, , 1993Hein, 2003, 2004;Wang et al, 2001;Myers and Griffiths, 2003;Hudson and Kaplan, 1985;Kececioglu and Gusfield, 1998;Gusfield, 2005a;Gusfield et al, 2004b,a;Nakhleh et al, 2003Nakhleh et al, , 2004Moret et al, 2004;Bansal, 2004, 2006a;Lyngso et al, 2005;Song et al, 2006;Myers, 2003).…”
Section: Rooted and Root-unknown Problemsmentioning
confidence: 99%
“…The incompatibility graph in Figure 2 has two components. Previously (Gusfield et al, 2004b;Gusfield, 2005a;Gusfield et al, 2007Gusfield et al, ,2004aBafna and Bansal, 2004), the non-trivial connected components of the conflict and incompatibility graphs were shown to be very informative, used both to derive efficient algorithms and to expose combinatorial structure in phylogenetic networks. The structural importance of the non-trivial connected components is further developed in the main result, presented next.…”
Section: Incompatibility and Perfect Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…Gusfield et al gave a biological justification for level-1 networks (which they call "galled trees") [9]. Minimising reticulations has been very well studied in the framework where the input consists of (binary) sequences [10] [11][23] [24]. For example, Wang et al considered the problem of finding a "perfect phylogeny" with a minimum number of reticulations and showed that this problem is NP-hard [25].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the task is to construct a rooted phylogenetic network from a set of binary sequences. The third is horizontal gene transfer networks, where the goal is to explain the discrepancies between gene trees and a species tree (e.g., Gusfield et al, 2007;Semple, 2007;Nakleh, 2009;van Iersel et al, 2010). The fourth is the construction of rooted phylogenetic networks from triplets (van Iersel et al, 2008;van Iersel and Kelk, 2011).…”
Section: Introductionmentioning
confidence: 99%